1997
DOI: 10.1046/j.1469-8137.1997.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of Salix to metal stress

Abstract: SUMMARYNine different clones of six species of Salix (Salix cordata Muhlenb. non Michaux, 5. fragilis L., S. caprea L., S. cinerea h., S. burjatica Nazarov. and 5. viminalis L.) and one hybrid (S. x calodendron Wimm.) were exposed to heavy metals in solution culture in an attempt to increase innate metal resistance. Resistance was estimated using comparative root measurements, and metal uptake was also studied. The first experiment entailed pretreatments with background nutrient solution, or 0-25 and 050 mg Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 39 publications
8
60
2
3
Order By: Relevance
“…The distribution pattern of Cu in plant parts was ranked in the order of roots>stems>leaves. Our results showed relatively high levels of Cu in the above-ground parts, especially in the aerial stems; similar results were reported by Punshon and Dickinson (1997). To the best of our knowledge, however, our results indicate that the Cu accumulation ability of the clones investigated here is far higher than those reported in other studies of the Salicaceae family.…”
Section: Variation In Cu and Zn Accumulationcontrasting
confidence: 56%
See 1 more Smart Citation
“…The distribution pattern of Cu in plant parts was ranked in the order of roots>stems>leaves. Our results showed relatively high levels of Cu in the above-ground parts, especially in the aerial stems; similar results were reported by Punshon and Dickinson (1997). To the best of our knowledge, however, our results indicate that the Cu accumulation ability of the clones investigated here is far higher than those reported in other studies of the Salicaceae family.…”
Section: Variation In Cu and Zn Accumulationcontrasting
confidence: 56%
“…Punshon and Dickinson (1997) reported that Salix fragilis accumulated Cu >300 μg/g DW in leaves, 25-150 μg/g DW in stems, and 300-1200 μg/g DW in roots. However, under some experimental conditions, relatively high Cu concentrations in aerial parts of the Salicaceae family were also recorded.…”
Section: Variation In Cu and Zn Accumulationmentioning
confidence: 99%
“…An exposure to dual combinations of metals in the solution culture increased Cd and Zn content in willow roots when supplied with Cu, but not when it was supplied with Zn. Root-bound Cu increased in all combinations (Punshon and Dickinson 1997). However, these element interactions are necessary to compare biomass yields.…”
Section: Resultsmentioning
confidence: 99%
“…Willows acclimation to toxic metals can be achieved by gradually increasing concentrations of heavy metals over 128 days rather than by short-term single pre-treatment. Increased resistance (especially to Cd) is attributable to reduced uptake (Punshon and Dickinson 1997). The interaction between Cd and Zn is either antagonistic or synergistic.…”
mentioning
confidence: 99%
“…Rooted cuttings of Salix sp. can be acclimated to metallic stresses in hydroponic conditions (Punshon and Dickinson, 1997). These studies have contributed to explain how the plants survive and grow in potentially toxic environments (Dickinson et al, 1992;Turner and Dickinson, 1993b).…”
Section: Mechanisms Of Resistance or Tolerance To Metals In Plantsmentioning
confidence: 99%